Quality standards for digital forensics: Learning from experience in England & Wales. (March 2020) - Tully, Gillian; Cohen, Neil; Compton, David; Davies, Gareth; Isbell, Roy; Watson, Tim
Abstract: The Forensic Science Regulator has the role of setting quality standards for forensic science in the Criminal Justice System (CJS) in England and Wales. The current requirement is for organisations carrying out digital forensics to gain accreditation to the international standard ISO/IEC 17025 and the Forensic Science Regulator's Codes of Practice and Conduct. The aim of this requirement is to embed a systematic approach to quality, including understanding methods, validating software and systems, understanding risks, ensuring that all involved in the crime scene to court process have the skills and competence they need and the appropriate equipment and environment for the work, and providing ongoing assurance of quality through audit and proficiency tests. However, the challenge of implementing the standards in digital forensics should not be underestimated, particularly in an environment where there is insufficient capacity to meet a growing demand for services in an area of increasing complexity and fragmented delivery. It is therefore timely to review available data to determine the extent to which accreditation to ISO/IEC 17025 is addressing quality issues in digital forensics and consider what changes and resources could be made available to assist with implementation of quality systems. Highlights: The Forensic Science Regulator sets quality standards in England & Wales. ISO 17025 is controversial for digital forensics. Review of data shows accreditation to ISO 17025 shows brings improvement. Central resources for ground truth data and validation would assist.